Estrategias pedagógicas utilizadas en la conservación de la lengua materna, en niños entre seis y 11 años del centro etnoeducativo rural san Silvestre de la comunidad indígena Kamëntsá del municipio de San Francisco departamento del Putumayo (2020)
This research was carried out in the Municipality of San Francisco located in the Putumayo department and had as its central axis to analyze the pedagogical strategies used by teachers and parents in the preservation of the mother tongue, this study was carried out with one of the indigenous communities belonging to this territory called the Kamëntsá ethnic group which is identified by the community's own customs and uses and which are considered as cultural heritage of the region, which is why the issue to be addressed caught the attention of the researchers, thus determining the It is necessary to focus a research study to be carried out with children between six and 11 years of age at the San Silvestre Rural Ethnoeducational Center, also considering that there is no history of this type of research in this Putumayo region.